Invisible forces: gender, race, and congressional staff. (1st January 2023) - Dittmar, Kelly
ABSTRACT: This project adopts theories of gendered and racialized professionalism to make visible and evaluate gender, race, and congressional staff as key and intersecting forces in the function and outcomes of legislative institutions. Drawing upon more than 60 interviews conducted with high-level women staffers who worked on Capitol Hill over the past 5 decades, it documents the influence of gender, race, and intersectional identities on staffers': experience of and adaptation to Capitol Hill; role in mediating the representation process; and engagement in institutional intervention. First-person accounts are used to demonstrate the utility of these theoretical frameworks for studying political professionals and to suggest future research that is attentive to legislative professionals, identity, and representation in political institutions.